Peptide Amyloids in the Origin of Life. Issue 20 (12th October 2018) - Greenwald, Jason; Kwiatkowski, Witek; Riek, Roland
Abstract: How life can emerge from non-living matter is one of the fundamental mysteries of the universe. A bottom-up approach to this problem focuses on the potential chemical precursors of life, in particular the nature of the first replicative molecules. Such thinking has led to the currently most popular idea: that an RNA-like molecule played a central role as the first replicative and catalytic molecule. Here, we review an alternative hypothesis that has recently gained experimental support, focusing on the role of amyloidogenic peptides rather than nucleic acids, in what has been by some termed "the amyloid-world" hypothesis. Amyloids are well-ordered peptide aggregates that have a fibrillar morphology due to their underlying structure of a one-dimensional crystal-like array of peptides in a β-strand conformation. While they are notorious for their implication in several neurodegenerative diseases including Alzheimer's disease, amyloids also have many biological functions. In this review, we will elaborate on the following properties of amyloids in relation to their fitness as a prebiotic entity: they can be formed by very short peptides with simple amino acids sequences; as aggregates they are more chemically stable than their isolated component peptides; they can possess diverse catalytic activities; they can form spontaneously during the prebiotic condensation of amino acids; they can act as templates in their own chemical replication; they have a structurally repetitive nature that enables them to interact with other structurally repetitive biopolymers like RNA/DNA and polysaccharides, as well as with structurally repetitive surfaces like amphiphilic membranes and minerals. Graphical abstract: Highlights : Short peptide amyloids may have played an important role in the origin of life on Earth as the first informational and catalytic entities. Amyloids can form under prebiotic conditions and are a plausible precursor to biological proteins. Amyloids have an inherent ability to interact with repetitive structures like membranes and DNA, bridging the prebiotic divide between life's main macromolecular structures.